PENGARUH STRATEGI PEMBELAJARAN KOOPERATIF SNOWBALLING PADA SEKOLAH MULTIETNIS TERHADAP KEMAMPUAN BERPIKIR KRITIS SAINS BIOLOGI SISWA SMP SAMARINDA - Elsje Theodora Maasawet (UNIVERSITAS MUHAMMADIYAH METRO, 2010)
The educational world has recently shown that there have been more and more educational observers and practisioners who care about education, particularly in trying to imporve the quality of education. Samarinda is among many other cities in Indonesia that has an ethnical variety. The number of ethnics found to have inhabited Samarinda are: Javanese, Banjarese, Buginese, Kutainese, Dayaks, Bataks, Ambonese, Manadonese, Chinese, Butonese, and Maduranese. The ethnical variety can inevitably trigger different problems confronted by the community, particularly the students’ ethincial background at schools. Survey showed that the VIII grade SMP students’ learning results in Samarinda was was still low, The learning strategy that can facilitate these multi-ethnical students will be very helpful in improving their learning results. The learning strategy that can be applied upon multi-ethnical students is the Snowballing cooperative learning strategy. This study aims to find out the influence of the Snowballing strategy upon critical thinking, cognitive learning results, and both of them play role in developing social attitude of multi-ethnic SMP students in Samarinda. Activites in the study consist of two stages: 1) survey research 2) the experiment-quasy research. Results of the Ancova tests indicated that there was a significant result of the Snowballing learning strategy upon the critical thinking, cognitive learning result and students. There was a significan influence of multi-ethnic condition upon critical thinking, cognitive learning result students. Javanese-ethnic students have the highest critical thinking ability and cognitie learning results compared to the their ethnic groups such as Banjarnese, Bugisnese, Kutainese and Dayaks. The SMP biology science teachers of Samarinda are suggested that they implement both snowballing cooperative strategies, as they have been proven to have been able to improve students’ critical thinking ability and cognitive learning results. Kata Kunci: Snowballing, Multietnik, Berpikir Kritis.